Policy model for development of tourism villages based on local wisdom towards self-reliant village in Pangandaran Regency, Indonesia - Yaya Mulyana Abdul Aziz; Abu Huraerah; M. Budiana; Regan Vaughan (Department of Government Studies Universitas Muhammadiyah Makassar, 2023)
The purposes of study are (1) analyze strengths, weaknesses, opportunities and threats of tourism village destination in Regency Pangandaran and (2) to formulate policy model for development of tourism villages based on local wisdom towards self-reliant village in Pangandaran Regency. This study uses a qualitative descriptive research method with approach studies case. Primary data collection techniques in the form of interviews, focus group discussion, observation and document study. Results of analysis of SWOT (strength, weakness, opportunity, threat) of tourism village destination in Pangandaran Regency, especially (a) Strength: (1) airport Nusawiru as access for tourist international and inter bus city or between province that has destination to Regency Pangandaran; (2) culture famous Sundanese friendly. (b) Weakness: (1) standardization policy opening and development destination tour new to district Pangandaran not yet available; (2) access good way not yet evenly on each destination existing tours; (3) readiness resource man for accept tourists and awareness will industry tourist not yet maximum. (c) Opportunity: (1) have many potency destination unexplored tourism; (2) existence track train fire and airport Nusawiru as well as Harbor Bojong Salawe; (3) training about tourism through extracurricular for learner and language foreign for society. (d) Threat: (1) stability nature and impact environment in implementation exploitation destination travel; (2) degradation score culture and potential leave inheritance existing culture. Policy model for development of tourism villages based on local wisdom towards independent villages include tradition, community empowerment and participation society.